All Days 2012
DOI: 10.2118/156013-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Co-deposition of Calcium Sulphate and Barium Sulphate and Developing Environmental Acceptable Scale Inhibitors Applied in HTHP Wells

Abstract: Calcium sulphate and barium sulphate are two major scales experienced in the oil and gas fields, especially when sea water breakthrough in the waterflood supported HTHP wells. Normally, studies have been focused on a single scale component. Seldom studies have focused on the co-deposition of calcium sulphate and barium sulphate. The importance of interference between calcium sulphate and barium sulphate deposition in the field, especially for the HTHP wells, has been ignored.In this paper, the interference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The results of this study showed that the effect of calcium sulfate solubility and the size of deposited scales take over the effect of barium sulfate solubility, so the intensity of permeability reduction in composite scale formation experiments increases. This result is in good agreement with the work of Liu et al (2012) which their experimental research showed that the intensity of composite BaSO 4 eCaSO 4 deposition in coil tube was clearly greater than the intensity of pure BaSO 4 and pure CaSO 4 scale deposition.…”
Section: Barium Sulfate Solubilitysupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study showed that the effect of calcium sulfate solubility and the size of deposited scales take over the effect of barium sulfate solubility, so the intensity of permeability reduction in composite scale formation experiments increases. This result is in good agreement with the work of Liu et al (2012) which their experimental research showed that the intensity of composite BaSO 4 eCaSO 4 deposition in coil tube was clearly greater than the intensity of pure BaSO 4 and pure CaSO 4 scale deposition.…”
Section: Barium Sulfate Solubilitysupporting
confidence: 92%
“…Immense amounts of information about these scales have been documented by Kan and Tomson (2012) of which a summary is presented in Table 1. A few studies (Sudmalis and Sheikholeslami, 2000;Chong and Sheikholeslami, 2001;Hennessy and Graham, 2002;Jones et al, 2004;Tung et al, 2004;Sheikholeslami, 2011;Liu et al, 2012) have been conducted to investigate composite scale formation. Sudmalis and Sheikholeslami (2000) stated that coprecipitation of CaCO 3 and CaSO 4 in static batch tests affects the thermodynamics and kinetics of single CaSO 4 and CaCO 3 as well as scale structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitation of these solids occurs as a result of changes in the ionic composition, pH, pressure and temperature of the brine. When water flooding method is applied for enhance oil recovery, then the problem of scale may occur right from water injection facilities to the producing well, and generally scale can occur during and after injection operation in the injector wellbore, near the injection well bottom hole, in the reservoir between the injector and producer, at the skin of producer well, in the producer wellbore, oil well casing, oil pipelines and other production facilities (Liu et al 2012;Dickson et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Scale is often defined as the precipitation from aqueous solution with inorganic sediments and scale deposition is a problem commonly existing in different processes in oilfield productions, for instance, water injecting, oil extracting, gathering and transporting, warming treatment, demulsification, crude oil dehydration and desalting, etc., meanwhile, the scale is prone to be appeared on the down hole, oil well casing, oil pipelines and other production equipments (Liu et al 2012;Dickson et al 2011). The scale deposition products in oilfield are mainly consisted of calcium carbonate, calcium sulfate, barium sulfate and strontium sulfate, iron, silicon sediment and other insoluble solids (Senthilmurugan et al 2011;Dickinson et al 2012) and the production of scaling is often due to the changes of thermodynamics conditions or the fluids incompatibility.…”
Section: Introductionmentioning
confidence: 99%